PERANAN PENYULUH TERHADAP PENGAMBILAN KEPUTUSAN PETERNAK DALAM ADOPSI INOVASI TEKNOLOGI PETERNAKAN DI KECAMATAN SANGKUB KABUPATEN BOLAANG MONGONDOW UTARA - Lamarang, Zulfikar. .; Sondakh, B F.J; Rintjap, Anneke K; Sajow, Adrie A (ZOOTEC, 2017)
THE ROLE OF EXTENSIONISTS TO THE DECISION OF FARMERS IN THE ADOPTION OF TECHNOLOGICAL INNOVATION FARMS IN SANGKUB SUB-DISTRICT, NORTH BOLAANG MONGONDOW DISTRICT.Extension activities is one of the goverment’s efforts that have an important role in improving knowledge, skills and attitude to livestock. Extension workers have an important role in the development of livestock breeding and improvement of livestock technology adoption process to farmers. The purpose of this study was to examine the role of extension workers in decision making farmers in the adoption of technological innovation farms in District of Sangkub North of Bolaang Mongondow regency. This research was done by survey method. Three  villages was selected using purposive method. Thirty respondents then selected  from breeder groups, which is done randomly. Data collection was done by interview, observation and documentation. The sources of data taken include primary data in the form of respondent identity, the number of livestock kept, the technology applied and the role of extension workers. Secondary data obtained from agriculture office of north Bolaang Mongondow regency, agricultural and forestry extension agency (BP3K) of Sangkub sub-district and central bureau of statistics Bolaang Mongondow. Data were analyzed by using scoring method and descriptive analysis. Result of the research indicate that the tendency of farmer appraisal to agriculture extension role as motivator, dynamic and facilitator in district of  Sangkub Regency of North Bolaang Mongondow  was optimal The results showed that the process of adoption of cattle ranchers in Sangkub sub-district North of Bolaang Mongondow  regency is varied from respondents who do not know about farming technology, have tried and already apply. And the role of extensionists have and influence on the dicision of farmers in the adoption of farm technology innovation in Sangkub sub-district.Keywords : The role of extensionists, Adoption process, Decision – making